Training transfer and transfer motivation: The influence of individual, environmental, situational, training design, and affective reaction factors - Bhatti, Muhammad Awais; Ali, Sharrifah; Mohd Isa, Mohd Faizal; Battour, Mohamed Mohamed (International Society for Performance Improvement, 2014)
The purpose of this study is to examine the effects of individual, environmental, training design, and affective reaction factors on training transfer and transfer motivation.To determine the relationship between these factors and their influence on training transfer and to test the model, the researchers collected data from employees in the Malaysian banking sector. Structural equation modeling with Amos 16 was used to test the model and determine the relationship.The study suggested that training stakeholders should manage the training program effectively.Transfer is maximized when trainees have social support, high performance self-efficacy, and transfer motivation.Stakeholders (e.g., trainers, trainees, supervisors, and peers) are important to the training transfer process, as are learner readiness, trainee reaction, instrumentality, and training retention.This study revealed that perceived content validity and transfer design work together and influence the trainee's performance self-efficacy. In other words, if trainers want to improve the performance self-efficacy level of trainees, they need to explain how the trainee can transfer the learned skills at the workplace and make sure the content of the training is similar to the actual job. The main objective of training programs is to align the employee's expertise with organizational goals. Organizations can achieve their desired objectives only when employees transfer the learned skills on the job.Unfortunately, employees often transfer only a small percentage of skills they have learned in training.To effectively manage their training programs, organizations need to identify and focus on the factors that resist effective training transfer.